Jatropha Oil - a Promising Source of Edible Oil - Jain, P. P.; Mahajan, Sushma (Indian Forester, 1996)
The toxicological studies, as given in the present paper, have revealed that no mortality of test animals was observed with refined/treated oil samples. However, sub-acute toxicity study, following oral route of the oil samples, may be required to arrive at fine conclusion. The preliminary studies, as given in the present paper, indicate that Jatropha curcas seed oil can be helpful in solving the problem of shortage of edible oils in the country, to some extent if a methodology is worked out to remove constituents responsible for inducing purging.